THE ROLE OF TECHNOLOGY IN MODERN TEACHING METHODS - Soliha Turgʻunova; Eshdavlatova Adiba Zafarovna (TADQIQOTLAR, 2026)
Abstract This study examines students’ opinions about technology-supported lessons. A survey was conducted among students of the English Faculty at SamSIFL. The aim was to understand how digital tools affect learning and classroom experience. The results show that most students find technology helpful and interesting. It makes lessons more engaging and easier to understand. However, some students mentioned problems such as internet issues and distractions.